2020
DOI: 10.1038/s41396-020-00843-4
|View full text |Cite
|
Sign up to set email alerts
|

Time-series transcriptomics from cold, oxic subseafloor crustal fluids reveals a motile, mixotrophic microbial community

Abstract: The oceanic crustal aquifer is one of the largest habitable volumes on Earth, and it harbors a reservoir of microbial life that influences global-scale biogeochemical cycles. Here, we use time series metagenomic and metatranscriptomic data from a low-temperature, ridge flank environment representative of the majority of global hydrothermal fluid circulation in the ocean to reconstruct microbial metabolic potential, transcript abundance, and community dynamics. We also present metagenome-assembled genomes from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 92 publications
(120 reference statements)
7
59
0
Order By: Relevance
“…Our survey of 18 metagenome assemblies from the North Pond crustal aquifer (Tully et al, 2018) using the FeGenie library confirmed the presence of previously reported iron oxidases (Figure 1) (Tully et al, 2018;Seyler et al, 2020), which we phylogenetically linked to Zetaproteobacteria (cyc2) and Rhodospirillaceae (foxE) (Supplementary File 2). Linking cyc2 to Zetaproteobacteria is important because this gene is highly diverse and is often encoded by taxa not known to be capable of iron oxidation; thus, only a handful of cyc2 genes have been experimentally shown to be iron oxidases (Castelle et al, 2008;Jeans et al, 2008;Barco et al, 2015;McAllister et al, 2020a;Keffer et al, 2021).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Our survey of 18 metagenome assemblies from the North Pond crustal aquifer (Tully et al, 2018) using the FeGenie library confirmed the presence of previously reported iron oxidases (Figure 1) (Tully et al, 2018;Seyler et al, 2020), which we phylogenetically linked to Zetaproteobacteria (cyc2) and Rhodospirillaceae (foxE) (Supplementary File 2). Linking cyc2 to Zetaproteobacteria is important because this gene is highly diverse and is often encoded by taxa not known to be capable of iron oxidation; thus, only a handful of cyc2 genes have been experimentally shown to be iron oxidases (Castelle et al, 2008;Jeans et al, 2008;Barco et al, 2015;McAllister et al, 2020a;Keffer et al, 2021).…”
Section: Resultssupporting
confidence: 85%
“…The Impact of Shifting Redox Conditions on Iron Cycling in the North Pond Aquifer Recent work, including metagenomic, metatranscriptomic, and colonization/poised-electrode experiments, provide evidence for iron oxidation within the North Pond aquifer. Metagenomic (Tully et al, 2018) and metatranscriptomic (Seyler et al, 2020) studies revealed the presence of genes associated with iron oxidation, specifically, cyc2 [encoding an outer membrane porincytochrome fusion; (Appia-Ayme et al, 1998;Castelle et al, 2008;Barco et al, 2015;He et al, 2017, Keffer et al, 2021] and foxE (encoding a periplasmic cytochrome; Croal et al, 2007;Pereira et al, 2017). Tully et al (2018) also reconstructed metagenomeassembled genomes (MAGs) affiliated with the iron-oxidizing Zetaproteobacteria, which are known to adapt to fluctuating O 2 concentrations and advective flow regimes (Chiu et al, 2017;Blackwell et al, 2020), further solidifying the presence and significant contribution that iron-oxidizing bacteria make to the aquifer community.…”
Section: Resultsmentioning
confidence: 90%
“…Given the lack of electron donors that could be paired with chemolithotrophy in our incubations, it is unlikely that rock-driven autotrophy is occurring in our experiments. Metagenomic and metatranscriptomic analysis of the same 2017 North Pond fluids used in our experiments showed more transcription of organotrophic genes than autotrophic genes across all sampling horizons, suggesting a microbial community utilizing organic carbon ( 28 ). Carbon fixation transcripts were most abundant in 1383C Middle and Deep where we also detected the highest rates of bicarbonate incorporation.…”
Section: Resultsmentioning
confidence: 74%
“…Gene abundances were normalized into transcripts per million (TPM) counts. The TPM values could be applied to metagenomes to remove the effects of total read counts and gene lengths when comparing the abundances of genes between samples [ 44 ].…”
Section: Methodsmentioning
confidence: 99%